The City and its Teachers. Perspectives from Art and Education - Alonso-Sanz, Dra. Amparo (Pulso. Revista de educación, 2015)
Review of the book: Huerta, R. (2015). La ciudad y sus docentes : miradas desde el arte y la educación.